Senegal : Fifth Review Under the Policy Coordination Instrument, Second Reviews Under the Stand-By Arrangement and the Arrangement Under the Standby Credit Facility, and Requests for Augmentation of Access, Waiver of the Nonobservance of a Performance Criterion, and Modification of a Performance Criterion and Quantitative Targets-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report ;, 2022)
The war in Ukraine is disrupting the post-pandemic recovery and exacerbating difficult policy trade-offs. This adds to a series of challenges facing the country, including the pandemic, the Ecowas sanctions against Mali, regional instability, and rising social demands. As a result, growth was revised down to 5 percent and inflation up to 5.5 percent in 2022. Medium-term prospects remain favorable with oil and gas production expected to start in 2023.